Impaired Lymphatic Drainage and Interstitial Inflammatory Stasis in Chronic Musculoskeletal and Idiopathic Pain Syndromes: Exploring a Novel Mechanism - Tuckey, Brian; Srbely, John; Rigney, Grant; Vythilingam, Meena; Shah, Jay (Frontiers in Pain Research, 2021)
A normal functioning lymphatic pump mechanism and unimpaired venous drainage are required for the body to remove inflammatory mediators from the extracellular compartment. Impaired vascular perfusion and/or lymphatic drainage may result in the accumulation of inflammatory substances in the interstitium, creating continuous nociceptor activation and related pathophysiological states including central sensitization and neuroinflammation. We hypothesize that following trauma and/or immune responses, inflammatory mediators may become entrapped in the recently discovered interstitial, pre-lymphatic pathways and/or initial lymphatic vessels. The ensuing interstitial inflammatory stasis is a pathophysiological state, created by specific pro-inflammatory cytokine secretion including tumor necrosis factor alpha, interleukin 6, and interleukin 1b. These cytokines can disable the local lymphatic pump mechanism, impair vascular perfusion via sympathetic activation and, following transforming growth factor beta 1 expression, may lead to additional stasis through direct fascial compression of pre-lymphatic pathways. These mechanisms, when combined with other known pathophysiological processes, enable us to describe a persistent feed-forward loop capable of creating and maintaining chronic pain syndromes. The potential for concomitant visceral and/or vascular dysfunction, initiated and maintained by the same feed-forward inflammatory mechanism, is also described.